SISTEM PEMESANAN HOTEL BERBASIS WEB MENGGUNAKAN METODE APRIORI DAN SIMPLE ADDITIVE WEIGHTING - Christopher Louis Fabian; Bagus Mulyawan; Janson Hendryli (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Web-based hotel application using Apriori method, the use of method based on the number of transactions that users do. Then look for the value of each itemset combination, which will then eliminated by the predetermined support value, after obtaining the result of elimination, then the association rule will be found to obtain a confidence value that will result in a percentage of each combination of facilities that have been eliminated.For the use of Simple Additive Weighting method, the data taken based on the total existing hotel, there are 250 hotels obtained from traveloka website. First, to find the SAW value determines the initial matrix to record the name of the hotel along with the given criteria, after which search fot the normalization matrix of the smallest and largest value divisions in each criteria, and the last step is the calculation of the vector weights can be determined by each user to determine priority criteria. After getting the result of the value of each hotel it will be sorted form the biggest point, so it will show the list of hotels with the biggest SAW points.